2002
DOI: 10.1034/j.1601-5223.2002.1360309.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of genetic diversity in kenaf (Hibiscus cannabinus L.) varieties based on analysis of agronomic and RAPD data

Abstract: Kenaf (Hibiscus cannabinus L.) is a fiber crop classified in the genus Hibiscus (Malvaceae), and has a great potential for its multipurpose utilization, in addition to its traditional usage. Varietal identification of kenaf is always problematic and knowledge on genetic diversity of kenaf varieties is also limited, which significantly hindered our effective utilization and conservation of the valuable kenaf germplasm. In order to find a proper method for identifying kenaf varieties and studying their variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Neutral genetic markers are also used in genetic differentiation analysis, but their reliability has been questioned when the evaluation of quantitative variation is an important research goal. Although it has been shown that the correlation between variation scored with such markers, and variation for adaptively important traits, is sometimes poor (Ennos et al 1997;Reed and Frankham 2001;Van Tienderen et al 2002;Bekessy et al 2003;Howe et al 2003) many studies have been successfully carried out to detect genetic diversity using such neutral markers (Cheng et al 2002;Hardy 2003;Shashidhara et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Neutral genetic markers are also used in genetic differentiation analysis, but their reliability has been questioned when the evaluation of quantitative variation is an important research goal. Although it has been shown that the correlation between variation scored with such markers, and variation for adaptively important traits, is sometimes poor (Ennos et al 1997;Reed and Frankham 2001;Van Tienderen et al 2002;Bekessy et al 2003;Howe et al 2003) many studies have been successfully carried out to detect genetic diversity using such neutral markers (Cheng et al 2002;Hardy 2003;Shashidhara et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…To date, RAPD analysis has been effectively utilized for determining the genetic diversity in many species, for example, tomato (Joshi et al, 2013) and oat (Ruwali et al, 2013). It has also been reported that the superiority of the molecular analysis data than the morpho-agronomic analysis for identification of different kenaf varieties (Cheng et al, 2002). Therefore, we have used this technique for detection of genetic diversity in different kenaf genotypes originated from 15 countries (Table 2), but cultivated in single tropical environment (Malaysia).…”
Section: Discussionmentioning
confidence: 99%
“…For RAPD analysis, five OPA primer sets described by Cheng et al (2002) were used in this study. The primers were synthesized by medigene Sdn Bhd, Malaysia.…”
Section: Rapd Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…RAPD has been reported capable of detecting the relative distance among the member of genus Hibiscus section Furcaria [20]. The genetic diversity of kenaf based on agronomic and RAPD data has been detected [21]. Characterization of flax collection by means of RAPD technique also has been done [19].…”
Section: Introductionmentioning
confidence: 99%